Tomato grafting onto Solanaceae genotypes to control bacterial wilt (Ralstonia solanacearum Smith 1896) - Silva Carvalho, Livia Talita da [UNESP]; Melo, Danilo Mesquita; Vargas, Pablo Forlan [UNESP]; Aguiar Santos, Helane Cristina; Ferreira, Jessica Vasconcelos (Univ Federal Goias, 2020)
The tomato cultivation in the Amazon is not feasible mainly due to the natural infestation of Ralstonia solanacearum in the soil. Preventive control through grafting has been one of the main alternatives to manage this problem. This study aimed to evaluate the compatibility of Solanaceae genotypes as rootstocks for 'Santa Clara' tomato, aiming to control the bacterial wilt. Five rootstocks were evaluated: cubiu; red jurubeba; jurubebao; commercial hybrid tomato rootstock Guardiao; and 'Santa Clara' tomato (self-grafting). In the seedling phase, characteristics of rootstock survival rate and compatibility were evaluated; while, in the field, that happened for survival rate, compatibility and fruit yield. In the seedling phase, Guardiao and red jurubeba showed the best performances. In the field, red jurubeba presented a low compatibility, although it obtained the best productive performance among the wild rootstocks. Guardiao obtained the best compatibility and yield among the studied rootstocks. Grafting is a viable technique for tomato production under soilborne disease conditions.
Keywords: Solanum stramoniifolium; Solanum crinitum; Solanum sessiliflorum